Water-based lithium-supplementing diaphragm and preparation method and application thereof

Through the preparation method of water-based lithium supplementation separators, the composite nanopowder is formed by ball milling and dispersed in deionized water, which solves the problems of material sensitivity and high cost of the existing lithium-ion battery lithium supplement technology, and achieves efficient lithium supplementation and low-cost production.

CN119905772AActive Publication Date: 2025-04-29SHAANXI RUIZHI NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510138325.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-29
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

The existing lithium-ion battery lithium supplement technology has high material sensitivity, environmental limitations in preparation, interface problems caused by by-products, and high costs, making it difficult to achieve industrialization.

Method used

The preparation method of a water-based lithium supplement membrane is adopted, and the lithium supplement agent, catalyst and conductive agent are mixed by ball milling to form a composite nanopowder, which is then dispersed in deionized water and evenly coated on the base film to prepare a functional membrane with high-efficiency lithium supplement performance.

Benefits of technology

The decomposition voltage of lithium supplement agent is significantly reduced, from 4.9V to below 3.7V, improving the energy density and cycle life of the battery cell, and achieving a green and low-cost production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905772A_ABST
    Figure CN119905772A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based lithium supplementing diaphragm as well as a preparation method and application thereof, and belongs to the technical field of lithium batteries. The aqueous lithium-supplementing diaphragm comprises a base membrane and a coating, the coating is coated on one side surface or two side surfaces of the base membrane, and the coating comprises a lithium-supplementing agent-conductive agent-catalyst composite material, a binder, a dispersing agent, a thickening agent, a wetting agent and the like. According to the prepared lithium supplementing diaphragm, lithium ions are separated from the lithium supplementing layer in the lithium supplementing diaphragm under the charging voltage of 3.7 V to supplement lithium for a battery cell, the capacity of a lithium ion battery is improved, the cycle life of the lithium ion battery is prolonged, the lithium supplementing requirement for lithium iron phosphate and a ternary system is met through low lithium supplementing voltage, meanwhile, the lithium supplementing diaphragm is prepared in an aqueous solution, and the lithium supplementing diaphragm has the advantages of being insensitive to the environment, low in cost and the like. And the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to an aqueous lithium-supplementing diaphragm and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used due to their high capacity and long life, but capacity decay still limits their development. Studies have found that the fundamental cause of lithium-ion battery cycle decay is the consumption of active lithium. To solve this problem, pre-lithiation has been proven to be an effective method that can compensate for the initial loss of active lithium by providing additional lithium sources.

[0003] At present, most of the research on lithium replenishment cells focuses on adding lithium replenishment agents to the positive and negative electrodes for lithium replenishment. There are many problems with positive and negative electrode lithium replenishment, which makes it difficult to industrialize. The negative electrode mostly uses lithium powder or lithium sheets, which has high requirements for process and environment, and there are safety risks. In positive electrode lithium replenishment, lithium replenishment agents are afraid of water and oxygen, are unstable, and increase the viscosity of the positive electrode slurry. The decomposition products are harder, which can easily cause problems such as diaphragm puncture.

[0004] In view of the above situation, the existing patent CN117936757A provides a lithium supplement material, a lithium supplement diaphragm and a preparation method thereof, using Li2O, Li2S, LFO, LNO lithium supplement agents as the core, ternary or quaternary active materials (such as NCM and NCA, etc.) as the coating layer, and NMP, DMC, etc. as solvent mixtures to prepare lithium supplement diaphragms, so that the lithium supplement layer can conduct electricity and conduct ions, which not only enhances the conductivity of the lithium supplement material, but also provides active Li ions and has sufficient lithium supplement, so that excellent and stable lithium supplement effects can be achieved. However, the lithium supplement agent and the ternary coating layer involved in the slurry are very sensitive to water and oxygen, the preparation environment is very restrictive to production, and the byproducts after the decomposition of the lithium supplement agent are easy to cause interface problems, the diaphragm is not easy to preserve, and the cost is too high.

[0005] CN118249037A discloses the preparation method and application of Li2C4O4-MXene composite material and lithium supplement diaphragm, wherein 3,4-dihydroxy-3-cyclobutene-1,2-dione and lithium carbonate are dissolved in water at a molar ratio of 1: (0.6-1.4), stirred to prepare Li2C4O4, then Li2C4O4 and MXene solution are mixed and spray-dried to form Li2C4O4-MXene composite material, the composite material and SuperP and PVDF are mixed in NMP to form slurry, the slurry is coated on the diaphragm, and the lithium supplement diaphragm is obtained by drying. In the actual production process, on the one hand, the oil system coating increases the cost too much; on the other hand, as a lithium supplement agent, lithium quartz Li2C4O4 decomposes to produce more CO2 gas, which will seriously cause abnormality of the battery cell, and the actual decomposition voltage is much greater than the theoretical decomposition voltage. When lithium ions are removed for lithium supplementation, the voltage reaches about 4.9V, so the lithium supplement diaphragm prepared above is difficult to be actually applied to the current battery cell system. Summary of the invention

[0006] The purpose of the present invention is to provide an aqueous lithium-supplementing diaphragm and a preparation method and application thereof, so as to solve the problems in the background technology.

[0007] To achieve the above object, the present invention provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Ball milling: Add the lithium supplement agent, catalyst MX and conductive agent into a ball mill and mill for 12 hours to make the catalyst and conductive agent effectively adhere to the surface of the lithium supplement agent, and spray dry the mixed slurry to obtain a composite material powder; S2, preparing lithium-replenishing coating slurry: adding the composite material powder obtained above into deionized water containing a dispersant for dispersion, adding a binder and a thickener thereto in sequence, and stirring to obtain a lithium-replenishing coating slurry; S3, coating: coating the lithium-replenishing coating slurry on at least one side of the surface of the base film, and obtaining the lithium-replenishing separator after curing and drying.

[0008] Preferably, in S1, by mass percentage, the lithium supplement agent accounts for 65-95%, the catalyst MX accounts for 1-20%, and the conductive agent accounts for 1-20%; the particle size of the lithium supplement agent is 0.5-2um, the particle size of the catalyst MX is 0.1-1um, and the particle size of the conductive agent is 0.01-0.2um.

[0009] Preferably, in S2, by mass percentage, the composite material powder accounts for 60-95%, the dispersant accounts for 0.1-10%, the binder accounts for 1-20%, and the thickener accounts for 1-20%.

[0010] Preferably, in S1, the lithium supplement is Li a H b Cc O d , wherein 1≤a≤2, 0≤b≤3, 1≤c≤4, 2≤d≤4; M in the catalyst MX is one of Ni, Fe, Mo, Ti and binary or ternary components thereof; X is one or more elements of O, Se, and S; and the conductive agent is one or more of carbon nanotubes, graphene, acetylene black, and Ketjen black.

[0011] Preferably, the lithium supplement agent is lithium oxalate Li2C2O4, the conductive agent is carbon nanotubes, and the catalyst is NiO.

[0012] Preferably, in S2, the dispersant is modified styrene maleic acid copolymer; the binder is polyacrylamide; and the thickener is sodium carboxymethyl cellulose.

[0013] The present invention also provides an aqueous lithium-replenishing diaphragm prepared by the above preparation method, wherein the aqueous lithium-replenishing diaphragm comprises a base film and a coating.

[0014] The present invention also provides an application of the above-mentioned aqueous lithium-replenishing membrane in a lithium-ion battery pack, wherein the lithium-ion battery pack includes a battery module, the battery module includes a lithium-ion battery, and the lithium-ion battery includes a positive electrode, a negative electrode, the aqueous lithium-replenishing membrane and an electrolyte.

[0015] The present invention controls the amount of catalyst and conductive agent to the above ratio, and the amount of MX metal compound as catalyst and conductive agent is relatively large, which is beneficial to Li a H b C c O d The lithium supplement decomposes Li at low voltage + Replenish lithium to improve the energy density and cycle life of the battery. a H b C c O d As a lithium supplement, its theoretical capacity is as high as 500mAh / g, showing great potential for lithium supplementation. However, in practical applications, Li a H b C c O d As a lithium supplement, there is a significant problem, the decomposition voltage is high, usually above 4.9V. Compared with the theoretical decomposition voltage of 3.0V, the overpotential is as high as about 2V. The reason is that during the charging process, the insulation of lithium oxalate will hinder the transmission of interfacial electrons, and the interfacial charge transfer process is the main reason for the high overpotential. a H b C c O dThe problem of high decomposition voltage of lithium supplement agent due to its insulation can be solved by mixing lithium supplement agent powder, catalyst powder and conductive agent together, ball milling them, and then spray drying them to obtain lithium supplement agent-conductive agent-catalyst composite material nanopowder. This can significantly increase the specific surface area of ​​lithium oxalate, improve interfacial electron transmission, reduce overpotential, accelerate electrochemical decomposition, and ultimately develop a functional diaphragm with high-efficiency lithium supplement performance.

[0016] Therefore, the aqueous lithium supplementation diaphragm and its preparation method and application of the present invention have the following beneficial effects: (1) The present invention selects Li a H b C c O d As a lithium supplement agent, it is compounded with catalyst MX and conductive agent to form a lithium supplement agent-conductive agent-catalyst nanopowder, which is dispersed in water with dispersants, binders, thickeners and other additives to form an aqueous dispersion, and evenly coated on porous PE and PP base films to prepare an aqueous lithium supplement diaphragm. Starting from the aqueous coating process, it has significant effects on environmental protection and cost reduction, achieving green and low cost; (2) The lithium replenishment membrane uses nano-scale catalysts and single-walled carbon nanotube conductive agents to successfully reduce the lithium decomposition voltage of the lithium replenisher from 4.9V to below 3.7V, meeting the current iron-lithium and ternary systems and solving the problem of excessive lithium voltage. The lithium replenishment membrane has the ability to decompose Li at a lower voltage. + Replenishing lithium sources to the battery cells can effectively improve the cycle life and capacity of the battery cells.

[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic structural diagram of an aqueous lithium-supplementing diaphragm of the present invention; Figure 2 is a morphology diagram of the aqueous lithium-replenishing coating in Example 1 of the present invention; Figure 3 This is a finished product diagram of the aqueous lithium-replenishing diaphragm of the present invention; Figure 4 This is a diagram showing the verification results of the lithium replenishment performance of the aqueous lithium replenishment membrane in the battery cell in Example 3 of the present invention. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below by means of the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, simplifications made without violating the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application and belong to the scope of protection of the present invention.

[0020] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.

[0021] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.

[0022] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.

[0023] Figure 1 It is a schematic structural diagram of the aqueous lithium-replenishing diaphragm prepared by the present invention.

[0024] Example 1 This embodiment provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-carbon nanotube-NiO composite material: 89g Li2C2O4, 5g NiO and 6g carbon nanotubes were added into a ball mill and ball milled for 12h to make NiO and carbon nanotubes effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0025] S2. Preparation of aqueous lithium supplement slurry: Add the above 100g Li2C2O4-carbon nanotube-NiO nanocomposite powder to 249.9g water containing 1g modified styrene maleic acid copolymer for high-speed dispersion, add 5g polyacrylamide and 0.96g sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-carbon nanotube-NiO composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0026] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0027] Figure 2 This is the SEM image of the aqueous lithium supplementation membrane prepared in this example. Figure 2 It can be seen that Li2C2O4-carbon nanotubes-NiO finally obtained a composite material with smaller particle size through ball milling and spraying. Carbon nanotubes and NiO are better combined with Li2C2O4, which is beneficial to the reduction of Li2C2O4 delithiation voltage.

[0028] Example 2 This embodiment provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-carbon nanotube-NiO composite material: 92g Li2C2O4, 2g NiO and 6g carbon nanotubes were added into a ball mill and ball milled for 12h to make NiO and carbon nanotubes effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0029] S2. Preparation of aqueous lithium supplement slurry: Add the above 100g Li2C2O4-carbon nanotube-NiO nanocomposite powder to 249.9g water containing 1g modified styrene maleic acid copolymer for high-speed dispersion, add 5g polyacrylamide and 0.96g sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-carbon nanotube-NiO composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0030] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0031] Example 3 This embodiment provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-carbon nanotube-NiO composite material: 86g Li2C2O4, 8g NiO and 6g carbon nanotubes were added into a ball mill and milled for 12h to make NiO and carbon nanotubes effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0032] S2. Preparation of aqueous lithium supplement slurry: Add the above 100g Li2C2O4-carbon nanotube-NiO nanocomposite powder to 249.9g water containing 1g modified styrene maleic acid copolymer for high-speed dispersion, add 5g polyacrylamide and 0.96g sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-carbon nanotube-NiO composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0033] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0034] Example 4 This embodiment provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-carbon nanotube-NiO composite material: 92g Li2C2O4, 5g NiO and 3g carbon nanotubes were added into a ball mill and ball milled for 12h to make NiO and carbon nanotubes effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0035] S2. Preparation of aqueous lithium supplement slurry: Add the above 100g Li2C2O4-carbon nanotube-NiO nanocomposite powder to 249.9g water containing 1g modified styrene maleic acid copolymer for high-speed dispersion, add 5g polyacrylamide and 0.96g sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-carbon nanotube-NiO composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0036] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0037] Example 5 This embodiment provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-carbon nanotube-NiO composite material: 86g Li2C2O4, 5g NiO and 9g carbon nanotubes were added into a ball mill and ball milled for 12h to make NiO and carbon nanotubes effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0038] S2. Preparation of aqueous lithium supplement slurry: Add the above 100g Li2C2O4-carbon nanotube-NiO nanocomposite powder to 249.9g water containing 1g modified styrene maleic acid copolymer for high-speed dispersion, add 5g polyacrylamide and 0.96g sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of lithium agent-carbon nanotube-NiO composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0039] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0040] Comparative Example 1 This comparative example provides a method for preparing a lithium supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-carbon nanotube composite material: 97g Li2C2O4 and 3g carbon nanotubes were added into a ball mill and milled for 12h to make the carbon nanotubes effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0041] S2. Preparation of aqueous lithium supplement slurry: Add the above 100g Li2C2O4-carbon nanotube nanocomposite powder to 249.9g water containing 1g modified styrene maleic acid copolymer for high-speed dispersion, add 5g polyacrylamide and 0.96g sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-carbon nanotube composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0042] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0043] Comparative Example 2 This comparative example provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-NiO composite material: 95g Li2C2O4 and 5g NiO were added into a ball mill and ball milled for 12h to make NiO effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0044] S2. Preparation of aqueous lithium supplement slurry: Add 100g of the above-mentioned Li2C2O4-NiO nanocomposite powder to 249.9g of water containing 1g of modified styrene maleic acid copolymer for high-speed dispersion, add 5g of polyacrylamide and 0.96g of sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-NiO composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0045] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0046] Comparative Example 3 This comparative example provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-NiO composite material: 100g Li2C2O4 and 0g NiO were added into a ball mill and ball milled for 12h to make NiO effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0047] S2. Preparation of aqueous lithium supplement slurry: Add 100g of the above-mentioned Li2C2O4-NiO nanocomposite powder to 249.9g of water containing 1g of modified styrene maleic acid copolymer for high-speed dispersion, add 5g of polyacrylamide and 0.96g of sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-NiO composite material in the coating accounts for 93.5%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 4.67%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0048] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0049] Comparative Example 4 This comparative example provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of Li2C2O4-carbon nanotube-NiO composite material: 84.55g Li2C2O4, 4.75g NiO and 5.7g carbon nanotubes were added into a ball mill and ball milled for 12h to make NiO and carbon nanotubes effectively adhere to the surface of Li2C2O4. The mixed slurry was spray dried to obtain nano composite material powder.

[0050] S2. Preparation of aqueous lithium supplement slurry: Add 95g of the above-mentioned Li2C2O4-carbon nanotube-NiO nanocomposite powder to 249.9g of water containing 1g of modified styrene maleic acid copolymer for high-speed dispersion, add 10g of polyacrylamide and 0.96g of sodium carboxymethyl cellulose in proportion, and stir evenly to obtain lithium supplement slurry. The mass of Li2C2O4-carbon nanotube-NiO composite material in the coating accounts for 88.83%, the mass of modified styrene maleic acid copolymer accounts for 0.93%, the mass of polyacrylamide accounts for 9.34%, and the mass of sodium carboxymethyl cellulose accounts for 0.9%.

[0051] S3, slurry coating: the lithium supplement slurry is evenly coated on at least one side of the surface of the 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium supplement separator.

[0052] Comparative Example 5 This comparative example provides a method for preparing an aqueous lithium-supplementing diaphragm, which specifically comprises the following steps: S1. Preparation of aqueous lithium supplement slurry: 89g Li2C2O4, 5g NiO, and 6g carbon nanotube CNT aqueous slurry are sequentially added to 249.9g water containing 1g modified styrene maleic acid copolymer for high-speed dispersion, 10g polyacrylamide and 0.96g sodium carboxymethyl cellulose are sequentially added thereto in proportion, and stirred evenly to obtain lithium supplement slurry. The mass proportion of Li2C2O4 in the coating is 88.83%, the mass proportion of modified styrene maleic acid copolymer is 0.93%, the mass proportion of polyacrylamide is 9.34%, and the mass proportion of sodium carboxymethyl cellulose is 0.9%.

[0053] S2. Slurry coating: The lithium-replenishing slurry is evenly coated on at least one side of a 12 μm PE base film by a coating machine, and then baked and dried to obtain a lithium-replenishing separator.

[0054] Figure 3The finished rolled-up aqueous lithium-replenishing diaphragm is shown in Figure 5, from left to right, Example 5, Comparative Example 3, and Example 3. Example 5 has the largest amount of conductive agent, resulting in a darker diaphragm color. Comparative Example 3 does not add conductive agent and catalyst, and is pure white. Example 3 adds an appropriate amount of conductive agent and catalyst, resulting in a gray color.

[0055] Performance Testing The aqueous lithium-replenishing diaphragm prepared in Examples 1-5 and Comparative Examples 1-5 was combined with electrodes and electrolyte to form a lithium-ion battery, and the combined lithium-ion battery was subjected to an overcharge test. Empty aluminum foil was used for the positive electrode, lithium sheet was used for the negative electrode, and 1.15 mol lithium hexafluorophosphate was dissolved in a mixed organic solvent of EC:DEC:VEC:PC:PS. The positive and negative electrodes, lithium-replenishing diaphragm, and electrolyte were assembled into a button cell. The test method was to charge the button cell at 0.1C to 4.99V, and the charging capacity data of the cell was observed in Table 1.

[0056] Table 1 Lithium replenishment battery test data

[0057] It can be seen from Table 1 that the aqueous lithium replenishing diaphragm provided by the present invention is used to replenish lithium for the battery cell to implement the lithium replenishment function. By comparing Example 1 with Comparative Examples 1-3, it can be seen that the catalyst and the conductive agent play a key role in the complete decomposition of the lithium replenisher at a low voltage. By comparing Example 1 with Comparative Example 4, it can be seen that the amount of the binder has no effect on the decomposition voltage and capacity of the lithium replenisher. By comparing Example 1 with Comparative Example 5, it can be seen that the combination of ball milling and spray drying processes has a greater effect on the decomposition voltage and capacity of the lithium replenisher, which allows the lithium oxalate lithium replenisher to replenish lithium for the battery cell at a lower voltage.

[0058] From the comparison of Examples 1-5, it can be seen that the more the catalyst is added, the lower the lithium de-lithiation voltage of the lithium supplement agent is, and the optimal addition amount of the catalyst MX in the coating is 7.8%. The more the conductive agent is added, the less effect it has on further reducing the lithium de-lithiation voltage of the lithium supplement agent. The conductive agent affects whether its lithium supplement capacity is fully released, and the optimal addition amount of the conductive agent in the coating is 5.6%.

[0059] Figure 4 This is a result diagram of the lithium replenishment performance verification of the aqueous lithium replenishment membrane in Example 4 in the battery cell. An empty aluminum foil is used as the positive electrode, lithium metal is used as the negative electrode, and the electrolyte is 1.15 mol lithium hexafluorophosphate dissolved in a mixed organic solvent of EC:DEC:VEC:PC:PS. The positive and negative electrodes, the lithium replenishment membrane of Example 4, and the electrolyte are assembled into a button battery. The test method is to charge the button battery cell at 0.1C to 3.8V and observe the charging capacity of the battery cell. The capacity at this time is the capacity released by the lithium replenishment membrane.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an aqueous lithium-supplementing diaphragm, characterized in that: The specific steps include: S1. Ball milling: Add the lithium supplement agent, catalyst MX and conductive agent into a ball mill and mill for 12 hours to make the catalyst and conductive agent effectively adhere to the surface of the lithium supplement agent, and spray dry the mixed slurry to obtain a composite material powder; S2, preparing lithium-replenishing coating slurry: adding the composite material powder obtained above into deionized water containing a dispersant for dispersion, adding a binder and a thickener thereto in sequence, and stirring to obtain a lithium-replenishing coating slurry; S3, coating: coating the lithium-replenishing coating slurry on at least one side of the base film to form a coating, and obtaining a lithium-replenishing separator after curing and drying.

2. The method for preparing an aqueous lithium-supplementing diaphragm according to claim 1, characterized in that: In S1, by mass percentage, the lithium supplement agent accounts for 60-98%, the catalyst MX accounts for 1-20%, and the conductive agent accounts for 1-20%; the particle size of the lithium supplement agent is 0.5-2um, the particle size of the catalyst MX is 0.1-1um, and the particle size of the conductive agent is 0.01-0.2um.

3. The method for preparing an aqueous lithium-supplementing diaphragm according to claim 1, characterized in that: In S2, by mass percentage, the composite material powder accounts for 40-97%, the dispersant accounts for 0.1-15%, the binder accounts for 1-30%, and the thickener accounts for 1-20%.

4. The method for preparing an aqueous lithium-supplementing diaphragm according to claim 1, characterized in that: In the S1, the lithium supplement is Li a H b C c O d , wherein 1≤a≤2, 0≤b≤3, 1≤c≤4, 2≤d≤4; M in the catalyst MX is one of Ni, Fe, Mo, Ti and binary or ternary components thereof; X is one or more elements of O, Se, and S; and the conductive agent is one or more of carbon nanotubes, graphene, acetylene black, and Ketjen black.

5. The method for preparing an aqueous lithium-supplementing diaphragm according to claim 4, characterized in that: The lithium supplement is lithium oxalate Li2C2O4, the conductive agent is carbon nanotubes, and the catalyst is NiO.

6. The method for preparing an aqueous lithium-supplementing diaphragm according to claim 1, characterized in that: In S2, the dispersant is modified styrene maleic acid copolymer; the binder is polyacrylamide; and the thickener is sodium carboxymethyl cellulose.

7. An aqueous lithium supplementation diaphragm, characterized in that: The aqueous lithium-replenishing diaphragm is prepared by the preparation method according to any one of claims 1 to 6, and the aqueous lithium-replenishing diaphragm comprises a base film and a coating.

8. The use of an aqueous lithium supplementation membrane as claimed in claim 7, characterized in that: The aqueous lithium-replenishing diaphragm is applied to a lithium-ion battery pack. The lithium-ion battery pack includes a battery module. The battery module includes a lithium-ion battery. The lithium-ion battery includes a positive electrode, a negative electrode, the aqueous lithium-replenishing diaphragm and an electrolyte.

Citation Information

Patent Citations

  • Lithium ion battery ceramic diaphragm and preparation method thereof

    CN112038550A

  • Composite lithium supplementing material and preparation method thereof, lithium supplementing coating and preparation method thereof, and lithium battery

    CN116799210A

  • Lithium supplement diaphragm, preparation method thereof and lithium ion battery

    CN119208920A

  • Composite catalyst for decomposing positive electrode material lithium supplement agent, preparation method and application

    CN119318982A

  • Lithium replenishment composite material and preparation method therefor, positive electrode sheet, separator, secondary battery, and electrical device

    WO2024145762A1

Cited By

  • Modified PE diaphragm with low decomposition voltage and high lithium supplement capacity and preparation method thereof

    CN121355518A